2023
DOI: 10.1038/s41598-023-32383-0
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and expressional studies of GaZnF gene to improve drought tolerance in Gossypium hirsutum

Abstract: Drought stress is the major limiting factor in plant growth and production. Cotton is a significant crop as textile fiber and oilseed, but its production is generally affected by drought stress, mainly in dry regions. This study aimed to investigate the expression of Zinc finger transcription factor’s gene (GaZnF) to enhance the drought tolerance in Gossypium hirsutum. Sequence features of the GaZnF protein were recognized through different bioinformatics tools like multiple sequence alignment analysis, phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Siddiqui et al (2021) reported that Se application improves the morphology of barley plant. Under drought stress, water scarcity leads to a decrease in seed yield components, including seed quantity per plant and seed size, resulting in reduced crop productivity (Ahanger et al, 2016;Batool et al, 2023). This is primarily due to water scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…Siddiqui et al (2021) reported that Se application improves the morphology of barley plant. Under drought stress, water scarcity leads to a decrease in seed yield components, including seed quantity per plant and seed size, resulting in reduced crop productivity (Ahanger et al, 2016;Batool et al, 2023). This is primarily due to water scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, (Kumar et al, 2021) identified quantitative trait loci (QTL) associated with plant height in cotton. Through marker-assisted selection, they successfully developed cotton lines with reduced plant height and increased yield potential (Zafar et al, 2022;Puspito et al, 2015;Batool et al, 2023;Hafeez et al, 2021;Aaliya et al, 2016). Another important morphological trait is branching pattern, specifically sympodial branches.…”
Section: Introductionmentioning
confidence: 99%